Avaliação comparativa de tratamentos termo-químicos visando a produção de absorvente a partir de resíduos agroindustriais para remoção de fenol em soluções aquosas - Pablo Diniz Rocha (2014)
The present study aimed to develop an alternative adsorbent based on corncob for removal of phenol from aqueous solution. This agroindustrial residue has a considerable potential for the production of adsorbents and is found in abundance in Brazil - world's third largest producer of corn. The corn cob was subjected to two different thermochemical treatments, based on Beker et al 2010, producing AC-1 and AC-2. In case of AC-1: i) 18h of drying at 105°C, ii) activation with phosphoric acid (85%); iii) 2h of carbonization in a muffle furnace at 500°C, iv) washing with sodium hydroxide until neutral pH, and v) 12h of drying at 105 °C. In case of AC-2: i) 18h of drying at 105°C, ii) activation with potassium hydroxide, iii) 0,5h of carbonization in a muffle furnace at 400°C, iv) washing with hydrochloric acid until neutral pH, and v) 12h of drying at 105°C. The performances of both AC produced were evaluated in batch adsorption experiments, in order to remove the phenol from aqueous solutions. Aiming at an increased use of coal from a laboratory scale to an industrial scale, an adsorption in fixed bed test was performed, as a wide variety of industries emit phenolic compounds in their wastewater. Procedures for surface characterization and analysis in infrared (IR), Boehm titration and point of zero charge were also conducted in order to understand the mechanism by which the adsorption occurs. The results showed that the treatment was effective in producing a selective AC to phenol removal. In batch adsorption experiments, it was observed that, for both AC, the adsorption capacity increased as the initial concentration of adsorbate in solution increased. AC-1 demonstrated a maximum capacity exceeding those reported in the literature for the commercial activated carbon. The models that best described the AC-1 adsorption process were the kinetic pseudo-second-order and Freundlich isotherm. Temkin isotherm best described AC-2 adsorption process. In the adsorption fixed bed test, saturation was reached more rapidly as the phenol concentration in the column entrance increased, for both AC. It was noticed that the longer column lifetime (without saturation) was obtained for the highest tested flow. The model that best described AC-1 adsorption process was Dose-Response. Bohart-Adams best described AC-2 adsorption process. The characterization by Boehm titration revealed the considerable presence of phenolic groups on AC-1 surface, and basic groups on AC-2 surface, which were confirmed by IR analysis, justifying the selectivity for phenolic compounds acquired in the activated carbon production process. These results support the existence of a great potential in agroindustrial wastes to use in the adsorbents production.